Analisis Kompetensi Pedagogik Guru: Tantangan dan Adaptasi Teknologi Dalam Pembelajaran Abad 21 Di SMA Negeri 2 Sulamu - Dominggus Eliaser Sinlae; Lisa Grasia Kailola; Hotmaulina Sihotang (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to analyze teachers' pedagogical competence in integrating 21st-century learning technology, identify barriers to technology adaptation, and describe teachers' adaptive strategies at SMA Negeri 2 Sulamu, Kupang Regency. The study used a qualitative approach with a single case study design within the interpretivism paradigm. Data were collected through in-depth interviews with 12 informants, observations of 10 teachers, documentation studies of 47 documents, and one Focus Group Discussion (FGD) session. Data analysis was conducted using the Miles, Huberman, and Saldaña model and strengthened through Braun and Clarke's thematic analysis. The results show that teachers' pedagogical competence is still dominated by pedagogical aspects compared to technology integration within the TPACK framework. In addition, this study found a gap between conceptual understanding and practical implementation of learning technology in the classroom. The obstacles faced by teachers are multilevel, encompassing macro, meso, and micro aspects, forming a spiral of constraint pattern. Teachers respond to these conditions through adaptive strategies such as a low-tech high-impact approach, peer-to-peer collaboration, and the integration of local wisdom in learning. This research provides a conceptual contribution by strengthening the concept of pedagogical resilience in the context of rural schools in Eastern Indonesia.